3U 큐브위성 표준 플랫폼의 개발 - 송수아(Sua Song); 이수연(Soo-Yeon Lee); 김홍래(Hongrae Kim); 장영근(YoungKeun Chang) (항공우주시스템공학회지, 2017)
This study proposes development of 3U CubeSat standard platform whose function and performance are verified via KAUSAT-5 development. 3U CubeSat platform specification was selected for the design of 3U Cubesat standard platform by examining existing CubeSat and state-of-art technology, and consequently a universally usable 3U CubeSat platform was designed. Standard platform was manufactured in 1.5U size and developed with a modular concept to be able to add and expand payloads and ADCS actuators for meeting the user's needs. In addition, in case of the power system, the solar panel, the battery, and the deployment mechanism are designed to be configured by the user. In the mechanical system design of a standard platform, subsystem and micro equipment functions/performance could be integrated and miniaturized on micro-sized PCBs and maximized electrical capability to accommodate multiple payloads. In the development of the 3U CubeSat, the satellite platform adopts the developed standard platform, which can reduce the cost and schedule for the whole satellite development by reducing the additional function verification. 본 연구에서는 3U 큐브위성의 표준 플랫폼을 개발하였으며, 개발된 표준 플랫폼을 3U 큐브위성인 한누리 5호에 적용함으로써 기능 및 성능을 검증하였다. 표준 플랫폼의 설계를 위해 기존 큐브위성 및 최신기술을 조사하여 3U 큐브위성 플랫폼 규격을 선정하였으며, 범용적으로 사용이 가능하도록 설계하였다. 표준 플랫폼은 1.5U 크기로 설계 및 제작되었고, 모듈러 개념으로 개발되어 사용자의 요구임무에 맞게 탑재체와 자세제어 구동기 등을 추가 및 확장시킬 수 있다. 또한 전력계의 경우 태양전지판, 배터리 및 전개 메커니즘을 사용자가 직접 구성하도록 설계하였다. 기계시스템 설계에서는 초소형 부품 및 서브시스템 기능/성능을 초소형 PCB에 집적 및 소형화하도록 하고, 다양한 탑재체를 수용할 수 있도록 플랫폼의 공간 활용률을 극대화하였다. 3U 큐브위성 개발 시, 위성 플랫폼은 개발된 표준 플랫폼을 채택하여 추가적인 기능 검증 등을 줄여 전체 위성개발에 대한 비용 및 일정을 단축시킬 수 있다.